AHP/ANP theory and its application in technological and economic development: the 90th anniversary of Thomas L. Saaty - Kou, Gang; Ergu, Daji (Technological and Economic Development of Economy, 2016)
"AHP/ANP theory and its application in technological and economic development: the 90th anniversary of Thomas L. Saaty." Technological and Economic Development of Economy, 22(5), pp. 649–650First published online: 02 Sep 2016